2004
DOI: 10.1017/s0022112004009759
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and breakup of a contracting liquid filament

Abstract: Contraction of a filament of an incompressible Newtonian liquid in a passive ambient fluid is studied computationally to provide insights into the dynamics of satellite drops created during drop formation. This free boundary problem, which is composed of the Navier–Stokes system and the associated initial and boundary conditions that govern the evolution in time of the filament shape and the velocity and pressure fields within it, is solved by the method of lines incorporating the finite element method for spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
194
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(224 citation statements)
references
References 60 publications
29
194
1
Order By: Relevance
“…more violent at later times. Such increasing oscillations of the tip speed were also observed at the edge of a contracting filament in the simulations of Notz & Basaran (2004) (figure 20). Depending on the Ohnesorge number, there were cases where the filament profiles they obtained were not single-valued functions of r near pinch-off.…”
Section: Low Oh Simulationssupporting
confidence: 54%
“…more violent at later times. Such increasing oscillations of the tip speed were also observed at the edge of a contracting filament in the simulations of Notz & Basaran (2004) (figure 20). Depending on the Ohnesorge number, there were cases where the filament profiles they obtained were not single-valued functions of r near pinch-off.…”
Section: Low Oh Simulationssupporting
confidence: 54%
“…In particular, for inviscid irrotational flows it has been shown that the simplified one-dimensional Euler equations exhibit a singularity before the point of breakup is reached 48 . Numerical simulations 49,50 show that in fact the free-surface of the droplet close to the singularity overturns.…”
Section: A Model For Inertio-elastic Pinchingmentioning
confidence: 99%
“…Recent and ongoing analytical studies concentrate on describing the pinching process asymptotically by utilizing the separation of radial and axial scales and mapping the dynamics to a class of self-similar solutions which are universal when inertia is present; notable studies include the work of Eggers (1993), Eggers & Dupont (1994), Papageorgiou (1995), Brenner et al (1996) for jets surrounded by a passive medium; Craster et al (2002), Craster et al (2003), Craster et al (2005), for surfactant-covered or compound jets; Conroy et al (2010), for core-annular arrangements in the presence of electrokinetic effects. Significant computational work has also been carried out with the aim of simulating the phenomena and evaluating the asymptotic theories (the latter are considerably less demanding numerically) -see Newhouse & Pozrikidis (1992), Pozrikidis (1999), Lister & Stone (1998), Sierou & Lister (2003), who simulate Stokes flows using boundary integral methods, and Ambravaneswaran et al (2002), Chen et al (2002), Notz et al (2001), Notz & Basaran (2004), Collins et al (2007), Hameed et al (2008) who compute the flow at arbitrary Reynolds number and in some instances include the effects of surfactants and electric fields -the extensions and novel aspects of the present work are outlined later.…”
Section: Introductionmentioning
confidence: 99%